2014
DOI: 10.1155/2014/238698
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Solitary Extramedullary Plasmacytoma

Abstract: A brief review of the salient literature is presented in regard to extramedullary plasmacytoma. The relevant clinical features, pathology, a n d methods of treatment are discussed. The eight cases seen by the authors are reviewed and their followup progress noted. The authors discuss a few interesting facets of extramedullary plasmacytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…But in general, survival of EMP is always better than bone plasmacytoma 11. In a review of 721 EMP cases by Alexiou et al , around 65% of patients had no recurrence and did not progress to MM, whereas 22% experienced recurrence, and 15% of cases evolved into MM 7. In another case series of 18 patients from Mayo Clinic showed that all EMP of the head and neck treated, median OS was 12.5 years with 5-year and 10-year survival rates of 88% and 55%, respectively, six patients developed MM or plasmacytoma at a distant site 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But in general, survival of EMP is always better than bone plasmacytoma 11. In a review of 721 EMP cases by Alexiou et al , around 65% of patients had no recurrence and did not progress to MM, whereas 22% experienced recurrence, and 15% of cases evolved into MM 7. In another case series of 18 patients from Mayo Clinic showed that all EMP of the head and neck treated, median OS was 12.5 years with 5-year and 10-year survival rates of 88% and 55%, respectively, six patients developed MM or plasmacytoma at a distant site 12.…”
Section: Discussionmentioning
confidence: 99%
“…We know radiation plays a major role in the management of EMP; however, surgery can be used as an alternative in few selected cases 4–6. Radical excision is often not possible in most of the cases because of the large tumour size, involvement of surrounding structures and poor cosmetic results with surgery 7. An interesting question therefore arises: after surgery, do we really need adjuvant radiation for local control?…”
Section: Discussionmentioning
confidence: 99%
“…Sasaki et al treated 67 patients with RT alone, and the 5-year and 10-year local control rates were 95% and 87%, respectively [ 14 ]. Another study revealed a 10-year local control of 88.9% with radiation alone [ 15 ]. The average dose of radiation should be at least 40–50 Gy given over 20–25 fractions.…”
Section: Discussionmentioning
confidence: 99%